A BRIEF ECOLOGICAL MOMENTARY INTERVENTION FOR GENERALIZED ANXIETY DISORDER: A RANDOMIZED CONTROLLED TRIAL OF THE WORRY OUTCOME JOURNAL. Issue 9 (7th April 2016) - LaFreniere, Lucas S.; Newman, Michelle G.
Abstract : Background: The efficacy of many cognitive behavioral component interventions has not been examined, with worry outcome monitoring among them. Methods: To address this issue, 51 participants with clinical levels of generalized anxiety disorder were randomly assigned to a treatment or control condition for 10 days. The treatment condition consisted of a brief ecological momentary intervention termed the Worry Outcome Journal ( WOJ ). WOJ participants recorded worries and tracked their outcomes, rating worry distress, interference, and expected outcome probabilities. Thought log (TL) control participants completed a record of their everyday thoughts and rated associated distress. All participants made four entries on paper each day when randomly prompted by text message. They then entered their paper contents online each night. After 30 days they reviewed their contents electronically and completed follow‐up measures. Results: Primary results revealed significant reductions in worry for WOJ users compared to TL users at postintervention. A marginally significant difference was found at 20‐day follow‐up and treatment gains were maintained. Secondary analyses showed no harmful increases in worry beliefs for WOJ users, as well as preliminary evidence for decreases in beliefs about the uncontrollability of thoughts in both groups. Conclusion: The WOJ may be a viable therapist‐independent treatment for reducing worry, even after only 10 days of use.